The determination of asteroid H and G phase function parameters using Gaia DR2. Issue 1 (21st April 2021) - Colazo, M; Duffard, R; Weidmann, W
ABSTRACT: The Gaia mission will provide the scientific community with high-quality observations of asteroids of all categories. The second release of Gaia data (DR2) was published in 2018 and consists of 22 months of observations of 14 099 known Solar system objects, mainly asteroids. The purpose of this work is to obtain a catalogue of phase function parameters ( H and G ) for all the asteroids that were observed during the Gaia mission and that were published in DR2. For this purpose, we introduce an algorithm capable of building this catalogue from the magnitude and UTC epoch data present in the DR2 data base. Because Gaia will never observe asteroids with a phase angle of 0° (corresponding to opposition), but with phase angles higher than 10°, we added data from ground observations (corresponding to small phase angles) and thus improved the determination of the H and G parameters of the phase function. We also built a catalogue of the parameters of the H, G 1 and G 2 phase function. We compared our results of the H, G functions with those of the Astorb data base and observed that the level of agreement is satisfactory.